2016
DOI: 10.1152/ajpheart.00338.2016
|View full text |Cite
|
Sign up to set email alerts
|

Ataxia telangiectasia-mutated kinase deficiency exacerbates left ventricular dysfunction and remodeling late after myocardial infarction

Abstract: Ataxia telangiectasia-mutated kinase (ATM), a cell cycle checkpoint protein, is activated in response to DNA damage and oxidative stress. We have previously shown that ATM deficiency is associated with increased apoptosis and fibrosis and attenuation of cardiac dysfunction early (1-7 days) following myocardial infarction (MI). Here, we tested the hypothesis that enhanced fibrosis and apoptosis, as observed early post-MI during ATM deficiency, exacerbate cardiac dysfunction and remodeling in ATM-deficient mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 29 publications
0
16
1
Order By: Relevance
“…This result is in clear contrast with the report from Daniel et al showing that ATM deficiency exacerbates cardiac dysfunction as well as cardiac fibrosis after MI even at the chronic phase. 29) Given that the mortality rate was higher (44%-61%) in the previous report compared to the present study (˜80%), it is suggested that the difference in the infarct size may explain the discrepancy between the results in both studies.…”
Section: Discussioncontrasting
confidence: 70%
“…This result is in clear contrast with the report from Daniel et al showing that ATM deficiency exacerbates cardiac dysfunction as well as cardiac fibrosis after MI even at the chronic phase. 29) Given that the mortality rate was higher (44%-61%) in the previous report compared to the present study (˜80%), it is suggested that the difference in the infarct size may explain the discrepancy between the results in both studies.…”
Section: Discussioncontrasting
confidence: 70%
“…Recently, it was shown that ATM is also involved in metabolic and cardiovascular complications when disrupted (39, 40). In addition, ATM kinase deficiency aggravated left ventricular dysfunction and remodeling late after myocardial infarction in mice (41). Interestingly, mice with ATM haplo-deficiency had decreased vascular endothelial growth factor production and impaired angiogenesis in response to myocardial infarction, leading to accelerated heart failure (41).…”
Section: Discussionmentioning
confidence: 99%
“…As indicated by a large number of researchers, myocardial fibrosis is associated with cardiac hypertrophy, myocardial infarction, hypertension, and heart failure (Daniel et al, 2016; Shimizu and Minamino, 2016; Wu et al, 2016). Myocardial fibrosis is a common pathological change during the development of various heart diseases.…”
Section: Discussionmentioning
confidence: 99%